Diversity and use of traditional medicinal plant species in Bantimurung-Bulusaraung National Park, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Husaini IPA, Maulany RI, Nasri N, Ngakan PO. 2022. Diversity and use of traditional medicinal plant species in Bantimurung-Bulusaraung National Park, Indonesia. Biodiversitas 23: 5539-5550. The people of Minasatene (Pangkep District) in Bantimurung-Bulusaraung National Park, South Sulawesi (Indonesia) have used traditional medicinal plants for many centuries. However, this local knowledge has not been recorded. This study aims to examine the diversity of plant species used to treat various ailments in the area. A set of semi-structured questionnaires was distributed to 60 respondents, consisting of traditional healers, elderly people, herb sellers and local people of Minasatene. This was used to obtain a demographic profile, vernacular names of plants and their uses, plant parts used, modes of preparation and methods of application. The diversity and use of the medicinal plant species in a traditional context were descriptively analyzed. The data were further extrapolated using Use Value (UV) to analyze the relative importance of plant species based on the number of uses; Fidelity Level (FL) to determine the specific uses of each plant species and preference over other species, and Informant Consensus Factor (ICF) to investigate an agreement between each group of diseases and related remedies. The study reveals that there were 74 species of medicinal plants belonging to 65 genera and 44 families being used as traditional medicines, which have been known to treat 54 ailments. Among the plant species, soursop (Annona muricata) had the highest UV (0,95), while the fig tree species, Ficus septica (100%) had the highest FL with the most frequent citation. From the data gained, it was found that skeletomuscular disorders had the highest ICF value (0,92).